White coat ceremony (VITAL, 2025)
Two white coat ceremonies were held this year, one on May 23 and the other on November 21. This ceremony is a symbolic act to celebrate the beginning of the internship, which for medical students is a step forward in their medical training.
Keywords: Internship; White coats; Medical training